1984
DOI: 10.1007/bf01876758
|View full text |Cite
|
Sign up to set email alerts
|

The genetic studies of familial amyloid polyneuropathy in the Arao district of Japan: II. Studies of genetic markers in blood

Abstract: SummaryBlood samples from 21 patients with familial amyloid polyneuropathy (FAP) and 81 normal family members among 7 affected families in Arao were tested for 9 blood group systems, 8 serum polymorphic proteins, 12 red cell polymorphic enzymes, and HLA. One of the most important findings was the existence of two relatively rare variants, i.e., group specific component Gc*IA2 and phosphoglucomutase PGMI*7 in 3 families. This observation suggests that the three genealogically independent families may have a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The finding that the structural abnormality (prealbumin 30 Val ~ Met) was identical, irrespective of the subject or the family is particularly valuable from two genetic aspects, First, it supports our view that the families afflicted with FAP in Arao may have a common ancestor (Sakoda et al, 1984), although there are nine genealogically independent families (Sakoda et al, 1983). If we combine the findings presented in this report with information on the distribution of two rare variants, i.e.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The finding that the structural abnormality (prealbumin 30 Val ~ Met) was identical, irrespective of the subject or the family is particularly valuable from two genetic aspects, First, it supports our view that the families afflicted with FAP in Arao may have a common ancestor (Sakoda et al, 1984), although there are nine genealogically independent families (Sakoda et al, 1983). If we combine the findings presented in this report with information on the distribution of two rare variants, i.e.…”
Section: Discussionsupporting
confidence: 55%
“…If we combine the findings presented in this report with information on the distribution of two rare variants, i.e. phosphogluc0mutase 7 and group specific component J (Sakoda et al, 1984), we can conclude that five of the nine families have a common ancestor. Whether or not 'the FAP gene in the Arao focuS is derived from the Protuguese reamins an interesting enigma (Andrade et al, 1970): Second, it lends credence to the view that the prealbumin variant is essentially concerned with the pathogenic mechanism of this gerteticatly determined neuropathic disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall penetrance, using Morton's method for late onset diseases, and discarding sibs below age 20, was calculated at 83.5% by Sakoda et al [1983]; in two families, whose pedigrees are shown, there are several instances of skipped generations, though age at death of the unaffected heterozygotes is not provided.…”
Section: Age-dependent and Incomplete Penetrancementioning
confidence: 99%